Development of the civil registration and vital statistics system in Nepal: making progress with civil registration, but lacking with vital statistics - United Nations Economic; Social Commission for Asia; the Pacific; Surender Pandey; Timothy Adair (Asia-Pacific Sustainable Development Journal, 2023)
Civil registration and vital statistics (CRVS) systems serve numerous legislative and administrative functions, and the resultant statistics provide valuable evidence for policy and monitoring purposes. Nepal has made progress in improving the civil registration component of the CRVS system, while the vital statistics component remains underdeveloped. The present article provides a review of progress in improving the CRVS system in Nepal with reference to global and regional contexts, emphasizing the statistical importance of CRVS systems, identifying possible causes for deficient vital statistics and recommending solutions for obtaining high-quality vital statistics from a CRVS system in an efficient and sustainable way.